Twittering informal learning and student engagement in first-year units - Leaver, Tama (Curtin University, 2012)
This chapter outlines an investigation into the utility of the online service Twitter as a tool for facilitating informal learning amongst first-year university students. Twitter was introduced to two first-year student groups, both taking the unit Web Communications 101; one group in a campus-based blended learning mode, which utilized traditional face to face tutorials, while the second version was delivered fully online via Open Universities Australia. The ways in which students used Twitter was recorded and examined, highlighting three main uses: socialising, resource-sharing and posing questions. Students’ perception of Twitter and its effectiveness as an informal learning tool was examined via a quantitative survey and a number of qualitative follow-up interviews. Notable differences emerged between the blended learning group and the fully online learners in terms of their attitude regarding Twitter use for facilitating informal learning. The chapter concludes with four recommendations regarding the implementation of Twitter as an informal learning tool for students.